2013
DOI: 10.1111/bij.12019
|View full text |Cite
|
Sign up to set email alerts
|

Morphological adaptation to coastal marshes in spite of limited genetic structure in the Neotropical passerineSpartonoica maluroides(Aves: Furnariidae)

Abstract: Tidal marshes present profound adaptive challenges to terrestrial vertebrates. For example, North American sparrows have relatively longer and thinner bills and darker dorsal plumage in coastal saltmarshes than in interior marshes. Bay‐capped wren‐spinetail (Furnariidae; Spartonoica maluroides) show a strong association with South American saltmarshes. We hypothesized that bay‐capped wren‐spinetail have similar morphological adaptations to North American sparrows to the saltmarsh environment, which would be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Recently, it has been reported that Wren-spinetail populations that breed in coastal marshes (dominated by Spartina densiflora) show phenotypic differences in bill morphology and plumage coloration (melanism) in respect to populations breeding at inland marshes (Cardoni et al 2013). This suggests that different selective forces would be acting on Wren-spinetail's traits, which may induce changes in important aspects of its life history, such as foraging (Cardoni et al 2013) or nesting strategies (this study).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Recently, it has been reported that Wren-spinetail populations that breed in coastal marshes (dominated by Spartina densiflora) show phenotypic differences in bill morphology and plumage coloration (melanism) in respect to populations breeding at inland marshes (Cardoni et al 2013). This suggests that different selective forces would be acting on Wren-spinetail's traits, which may induce changes in important aspects of its life history, such as foraging (Cardoni et al 2013) or nesting strategies (this study).…”
Section: Discussionmentioning
confidence: 69%
“…Several studies have shown that some bird species have adapted to the conditions presented by the marshes, for example, increment in beak size to increase heat body loss (Greenberg et al 2012), changes in the performance of the song as mating signals (Ballentine 2006), changes in body sizes (Greenberg & Droege 1990, Grenier & Greenberg 2006, and plumage melanism (Greenberg & Droege 1990). Recently, it has been reported that Wren-spinetail populations that breed in coastal marshes (dominated by Spartina densiflora) show phenotypic differences in bill morphology and plumage coloration (melanism) in respect to populations breeding at inland marshes (Cardoni et al 2013). This suggests that different selective forces would be acting on Wren-spinetail's traits, which may induce changes in important aspects of its life history, such as foraging (Cardoni et al 2013) or nesting strategies (this study).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetation profile represents an averaged profile of Bahía Samborombón and Laguna Mar Chiquita Estuaries and Coasts habitats was the bay-capped wren-spinetail, a furnarid species (Cardoni et al 2012). Bay-capped wren-spinetail also use other habitats along their distribution (Cardoni et al 2013), but show a strong association with South American saltmarshes (Isacch et al 2004;Isacch and Cardoni 2011;Cardoni et al 2011). In addition, comparisons of coastal and inland marsh populations show significant phenotypic differences in bill shape and plumage coloration (melanism), a convergent pattern with North American sparrows (Cardoni et al 2013), suggesting that there are strong selective pressures associated with saltmarsh environments.…”
Section: Discussionmentioning
confidence: 99%
“…Mauck & Burns () further showed that bill morphology in flowerpiercers has been highly labile and argued that differences in ecomorphology, behaviour, and habitat use likely account for the local coexistence of several species in this group at tropical sites. The evolutionary lability of avian bills and its possible influence on diversification is revealed by detailed work at a microevolutionary scale on Darwin's finches (Grant, Grant & Petren, ) and in the furnariid Spartonoica maluroides (Cardoni et al ., ), which show divergence in bill morphology associated with adaptation to different food supplies and contrasting environments.…”
Section: Introductionmentioning
confidence: 99%